The Influence of Management Information Systems on the Strategic Planning Process in Libyan Service Organizations - Elganidi, Emhemed Jamal (2010)
Management Information System and strategic planning process are key part of the business success and organizational effectiveness. Management Information System is comprised of MIS outputs, integration and coordination (MIS), and Quality of information. This study investigates the influence of management information system on strategic planning process in Libya. Data were collected from executive in 21 organizations. Descriptive statistics were calculated and correlation analysis and regression analysis was used to test the hypothesized relationships.